#TITLE_ALTERNATIVE# - ASWAMEDHA (NIM 10202007), AGUNG
Implementation of temperature control system for isolated room system has already reached many aspects in our life. One of the problems that often a rises on such system is instability, which usually occurs because of the conventional control design. This kind of design does not have the ability to control a system with proper action. Stability in control system holds very crucial importance. This is because performance of the control system relies heavily on it. On this final project, we will demonstrate the stability of a temperature control system which based on fuzzy logic to handle dynamical temperature change (random change on temperature value at set point).